2015
DOI: 10.1161/jaha.115.002122
|View full text |Cite
|
Sign up to set email alerts
|

Survival After Out‐of‐Hospital Cardiac Arrest in Children

Abstract: BackgroundLittle is known about survival after out‐of‐hospital cardiac arrest (OHCA) in children. We examined whether OHCA survival in children differs by age, sex, and race, as well as recent survival trends.Methods and ResultsWithin the prospective Cardiac Arrest Registry to Enhance Survival (CARES), we identified children (age <18 years) with an OHCA from October 2005 to December 2013. Survival to hospital discharge by age (categorized as infants [0 to 1 year], younger children [2 to 7 years], older childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
68
3
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(80 citation statements)
references
References 22 publications
(40 reference statements)
6
68
3
3
Order By: Relevance
“…Pediatric OHCA due to external causes accounted for 46.4% in this registry. This prevalence was higher compared with that in previous reports: 30.5% in Japan, 6) 17.2% in the United States, 23) and 34.2% in Australia. 24) Additionally, only two children received shocks delivered through a public-access AED.…”
Section: Discussioncontrasting
confidence: 72%
“…Pediatric OHCA due to external causes accounted for 46.4% in this registry. This prevalence was higher compared with that in previous reports: 30.5% in Japan, 6) 17.2% in the United States, 23) and 34.2% in Australia. 24) Additionally, only two children received shocks delivered through a public-access AED.…”
Section: Discussioncontrasting
confidence: 72%
“…1,23 We did not include sex or socioeconomic status, because previous researchers have suggested that they are unrelated to survival in OHCA. 2,4,24 The model for injured patients included injury severity score, a negative predictor of survival in trauma. 19 We investigated whether survival could be moderated by teaching hospital status among noninjured patients, hypothesizing that treatment at a teaching hospital might be associated with a survival advantage for children with OHCA.…”
Section: Main Analysesmentioning
confidence: 99%
“…3,7 Despite improvements in regional care and treatment algorithms for cardiac arrest, survival has not improved over the last decade. 4 Children with both in-hospital cardiac arrest and OHCA have been shown in some studies to have improved outcomes at pediatric hospitals. 8 -10 However, it is unclear if the improved outcomes are due to significant differences between patients presenting to pediatric versus general emergency departments (EDs).…”
mentioning
confidence: 99%
“…1,2 Survival from pediatric out-of-hospital cardiac arrest (P-OHCA) has typically been estimated between 6–12% and, when compared to adults, survival is lower in infants and higher in adolescents. 1,35 …”
Section: Introductionmentioning
confidence: 99%